DNA methylation abnormalities in atherosclerosis - Samira Tabaei; Seyyedeh Samaneh Tabaee (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Atherosclerosis is a complex disease with involvement of intermediate-, large-sized arteries. Atherosclerosis is characterized by the accumulation of vascular lipids, immune system activation, inflammation, oxidative stress and oxidized low-density lipoproteins (LDLs), endothelial cell (EC) activation, arterial smooth muscle cell (SMC) proliferation, macrophage activation and foam cell formation that cause endothelial dysfunction. DNA methylation is one of important epigenetic mechanisms which changes gene expression. It has been evident that this mechanism plays an important role in the initiation and propagation of atherosclerosis. Furthermore, DNA methylation is a crucial and distinct mechanism that modulates genes governing cell proliferation, thereby connecting environmental insults with gene expression. This study represents many atherosclerosis-related genes which are regulated through DNA methylation mechanism. Although the role of epigenetics in atherosclerosis is at their infancy. Nevertheless, various studies demonstrated that DNA methylation involvement in this disease is undeniable. DNA methyltransferases are the main player of the smooth muscle cell proliferation, endothelial cell integrity, as well as arteriosclerosis formation. In this review, we focus on recent achievements in the functional and description interpretation of the DNA methylation pattern of cells and tissues implicated in atherosclerosis. Besides, we discuss the association of DNA methylation with oxidative stress, hyperhomocysteinemia (HHcy), ageing, and inflammation in the development and pathogenesis of atherosclerosis.